Bringing together coproduction and community participatory research approaches: Using first person reflective narrative to explore coproduction and community involvement in mental health research - Colin King; Steve Gillard (Wiley, 2019)
Abstract Background A growing literature explores the coproduction of research knowledge. Barriers to coproduction in mental health research have been identified, especially for the people from marginalized communities. There is an established body of participatory research that has potential to inform coproduction in mental health research. Objectives To explore and articulate how learning from community participatory approaches to research enable barriers to knowledge coproduction to be overcome in mental health research. Setting An evaluation of a primary care mental health service, led by an experienced survivor researcher, supported by a health service researcher and involving a team of community co‐researchers. Design Cycles of reflective writing (first‐person narrative) by the authors, and feedback from the co‐researcher team, on their experiences of undertaking the evaluation were used to explore the ways in which community actors, including those from marginalized communities, might be meaningfully involved in producing research knowledge about mental health services. Results A space was created where community co‐researchers, including those from traditionally marginalized communities, felt safe and empowered to move beyond essentialized "service user" identities and bring a range of skills and expertise to the evaluation. There was meaningful rebalancing of power between traditional university and community roles, although the issues around leadership remained complex and more could be done to explore how our different experiences of race and mental health shape the research we do. Conclusions Potential was demonstrated for participatory research approaches to inform coproduction of knowledge in mental health research that fully reflects the diversity of identity and experience.